THE DEVELOPMENT OF COOPERATIVES IN MALAYSIA: HISTORICAL EVOLUTION, CHALLENGES, AND FUTURE DIRECTIONS - Hamzah, Siti Maslina; Yusoff, Mohd Nor Hakimin (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The cooperative movement in Malaysia has played a vital role in supporting socioeconomic development, poverty alleviation, and community empowerment since its inception during the colonial era. From its early focus on credit societies, cooperatives have expanded into agriculture, retail, housing, and services, aligning with national economic policies and reforms after independence. This paper aims to conceptually examine the historical development, current challenges, and future prospects of cooperatives in Malaysia. Using a systematic literature review (SLR), recent studies were synthesized to explore issues such as governance, innovation, sustainability, and alignment with Malaysia’s Shared Prosperity Vision 2030. Findings indicate that while cooperatives remain essential for inclusive growth, they face persistent gaps in governance, financial literacy, entrepreneurial orientation, and digital readiness. The paper contributes by providing a critical review of cooperative development in Malaysia and offering recommendations for policy, practice, and further research.